Aplikasi Monitoring Dan Evaluasi Pada Taman Kanak-Kanak Binaan Dharma Wanita Persatuan Kabupaten Sumbawa Dengan Metode Agile - Cece Listiana Umbara; Shinta Esabella; Eri Sasmita Susanto; Farida Idifitriani (Jurnal Gemilang Informatika (GIT), 2024)
Kindergarten Assisted by Dharma Wanita Persatuan Sumbawa Regency is an educational institution part of the Dharma Wanita Persatuan Foundation of Sumbawa Regency. The utilization of digital technology in monitoring and evaluating DWP Assisted Kindergarten activities is still done manually. This research aims to develop a Monitoring and Evaluation Application with the Agile Method at the Dharma Wanita Persatuan Assisted Kindergarten of Sumbawa Regency, which aims to produce a web-based application with an attractive appearance with additional features, namely the activity menu, inventory menu, and report menu. The data collection methods used were observation, interview, and literature study. This application was built using the agile method software development methodology, with structured modeling, codeigniter framework and PHP programming language and black box testing. The result of this research is a web-based monitoring and evaluation application for kindergarten. It is hoped that this application can help the monitoring and evaluation process of kindergartens assisted by DWP Sumbawa Regency more effectively and efficiently